Improving Short Story Writing Skills using Ndarboy Genk Music Videos as Media - Prihandono, Fajar Agustia; Rejokirono (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
This study addresses the significant challenge of low student motivation and achievement in cerkak (Javanese shortstory) writing at SMK Negeri 2 Depok Sleman, where 73.5% of Class XI students failed to meet the MinimumCompleteness Criteria (KKM). Utilizing the principles of sociocultural mediation and intrinsic motivation, thisClassroom Action Research (CAR), employing the Kemmis and McTaggart model, aimed to enhance students’writing skills by using music video clips from the popular popdut band, Ndarboy Genk, as an inspiring and culturallyrelevant medium. The research was structured across pre-cycle, Cycle I, and Cycle II, with data collected fromobservations and quantitative analysis of student writing products. The findings show a progressive and significantimprovement: student mastery increased from 26.47% (average score 68) in the pre-cycle to 67.65% (average score73) in Cycle I, culminating in 85.29% mastery (average score 78) in Cycle II. The improvement between cycles wasattributed to the corrective actions taken, notably enhanced teacher scaffolding focusing on narrative structure,improved time management, and better technical preparation. The cultural and contextual relevance of the NdarboyGenk media proved highly effective in boosting student engagement, serving as a powerful creative stimulus thatfacilitated theme development and emotional depth in their narratives. This study concludes that implementingculturally relevant audiovisual media, such as Ndarboy Genk's video clips, is an effective and innovativepedagogical strategy for significantly improving both the technical skills and engagement in Javanese languagewriting. It demonstrates the critical role of popular culture in acting as a motivational scaffold within local languageeducation.